Measurement of the tt[over] production cross section in pp[over] collisions at sqrt(s)=1.96 TeV. - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
We measure the tt[over] production cross section in pp[over] collisions at sqrt(s)=1.96 TeV in the lepton + jets channel. Two complementary methods discriminate between signal and background: b tagging and a kinematic likelihood discriminant. Based on 0.9 fb(-1) of data collected by the D0 detector at the Fermilab Tevatron Collider, we measure sigma(tt[over])=7.62+/-0.85 pb, assuming the current world average m(t)=172.6 GeV. We compare our cross section measurement with theory predictions to determine a value for the top-quark mass of 170+/-7 GeV.